The synthesis of a gold nanodisk–molecular layer–gold film vertical structure: a molecular layer as the spacer for SERS hot spot investigations. (8th December 2016) - Chang, Yu-Hsu; Hsu, Wen-Hsin; Wu, Song-Lun; Ding, Yung-Chin
Abstract : 3D structures of Au nanodisk–molecules–Au film are synthesized for a systematic measurement of SERS hot spots. Abstract : The objective of this research is to conduct a systematic measurement of hot spots formed between a gold (Au) nanodisk and an Au film using surface-enhanced Raman scattering (SERS). The dip-pen nanolithography and wet etching methods are used to fabricate sandwich structures with a self-assembled monolayer (SAM) or a polymer embedded between vertical Au nanodisks and the Au substrate. A flat polymer, which acts as a spacer, is synthesized via graft polymerization. The gap between the Au nanodisks and Au film is adjusted to the range from 2.4 to 12.1 nm by forming a SAM and repeating the graft polymerization. The SERS molecules, 4-mercaptobenzoic acid, are chemically bonded to the sidewalls of the Au nanodisks in order to observe the coupling interaction in the dipole of SERS while changing the gap size. According to the experimental results, the degree of field enhancement is greatly dependent on the dimensions of the gap. The greatest enhancement is reached when the gap distance is 3.8 nm, and no coupling effect is observed when the gap distance is more than 12 nm.